Substantiation of early teaching of technical and tactical training in girls boxing - Vorontsov, A. (Scientific Journal of Polonia University, 2022)
The article presents the substantiation of early training of technical and tactical training of girls who deal with boxing. Methods. Theoretical analysis of special and scientific literature, educational programs on sports and combat martial arts, generalization of data. Results. Considered: World trends in sports in general in gender, the chronology of the formation of women's boxing in the world, trends in the development of girls boxing in Ukraine and Europe. The theoretical analysis of physiological possibilities of girls to early mastering of techniques and tactics in boxing. Proved the ability to teach girls technical and tactical training (TTP) in boxing earlier than indicated in the training programs in boxing. It has been studied age qualification in the educational program of Children's and youth sports schools (CYSS) from admission to sports martial arts and boxing. A comparison of age qualification is made when taking on boxing and combat martial arts of girls. It have been studied normative requirements of leading countries in Europe in a girls boxing with transmitted to the following stages of preparation in the CYSS. It is determined that criteria only with the assessment of physical training and the indicated sports outcome on competitions during the year are not enough to transfer to the next year. Conclusion. The results of the theoretical analysis have proved to be expedient to decrease the age qualification for girls when enrolled to the boxing department of CYSS. It has been determined the great consideration of TTP level when transferring to the next year of study in the CYSS. The need to create author's techniques for assessing TTP in girls.